Implementasi Sensor Warna Pada Robot Lengan Pemindah Barang Menggunakan Inverse Kinematics: English - Istiqlal Farozi; Rizal Maulana; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The development of technology in today's era is very fast, especially in the world of robotics. Therefore, many large companies are competing in making robots that can help ease the burden on humans in their activities, ranging from daily activities to activities in the industrial world. The robot that is commonly used in the industrial world is an arm robot, this robot can help in minimizing mistakes made by humans and make work faster. In setting the movement, the robot can use the Inverse kinematics method. This method can adjust the robot's movement to the coordinates that have been determined. The research aims to make a four DOF arm robot, equipped with an Arduino UNO microcontroller and servo motor servo and TCS3200 color sensor. From the results of the study found that the color sensor can distinguish the colors that have been determined namely red, green and blue precisely. For testing the accuracy of angles without using the method obtained an average in servo1 of 17.74%, servo2 of 16.97% and servo3 of 15.85%. While the angular accuracy testing using the Inverse kinematics method obtained an average of servo1 of 21.45%, servo2 of 21.45% and servo3 of 13.46%. Testing the angular accuracy by comparing the formulas of forward kinematics and inverse kinematics obtained a difference of degrees between 0 - 7.95â°. And in the test of time in achieving the intended coordinate points obtained an average value of 7,094s to move the red cube, 7,518s for the green cube and 8.84s to move the blue cube. From the research it was concluded that the robot arm can make movements with several combinations using inverse kinematics with a success rate of 100%.